High-temperature annealing of ZnO nanoparticles increases the dissolution magnitude and rate in water by altering O vacancy distribution. (September 2019) - He, Hongping; Cao, Jianglin; Fei, Xunchang; Duan, Ning
Abstract: The effects and mechanism of high-temperature annealing, a frequently-used strategy to modulate the properties of nanoparticles (NPs), on the dissolution of zinc oxide (ZnO) NPs are investigated in this study. The results show that annealing increases the ZnO NPs dissolution magnitude via increasing O vacancy abundance on the surface and in the bulk crystal. The face-dependent distribution of O vacancy is revealed by characterizing ZnO single crystal, and the (000-1) face has a higher abundance than the (10-10) face. Particularly, O vacancy abundance in the bulk (000-1) is about 3 times higher than in the bulk (10-10). Annealing further strengthens the face-dependence of O vacancy distribution, therefore both raw and annealed (000-1) faces contribute dominantly to the dissolution of ZnO NPs. Typical topographies of the surface defect sites on the (000-1) face and their evolutions during dissolution are collected. Annealing promotes the formation of larger and deeper etching pits. Elevated solution temperature and annealing synergize to further accelerate ZnO dissolution. The dissolution behaviors of ZnO NPs with different annealing statuses, surface properties, and solution temperatures investigated in this study have potential implications to the evaluations of environmental fate and risk of metal oxide NPs. Highlights: Annealing increases ZnO NPs dissolution via increasing O vacancy abundance. Higher O vacancy abundance determines more dissolution from (000–1) facet. Annealing enhances facet dependence of O vacancy distribution from surface to the bulk. Elevated H2 O temperature and annealing synergize to accelerate ZnO NPs dissolution. This study has implication to evaluate environmental fate and risk of metal oxide NPs.